Cost of Quality Pilot: A Systematic Methodology for Examining the Cost of Pressure Injury. Issue 2 (March 2020) - Polancich, Shea; Miltner, Rebecca; Poe, Terri; Williamson, Jason; Vander Noot, Ross; Shirey, Maria
Abstract : ABSTRACT: Health care costs in the United States are considerable, and total national cost of preventable adverse events in the United States ranges from billions to trillions of dollars annually. Achieving the highest quality of health services requires delivering care that mitigates the risk of patient adverse events. Pressure injuries are a significant and costly adverse event. Mitigating or eliminating harm from pressure injuries not only improves quality and increases patient safety but also decreases costs of care. The purpose of this article is to pilot a systematic methodology for examining the differences in the cost of care for a subset of patients with and without hospital-acquired pressure injuries in an acute care setting.